Penatalaksanaan Fisioterapi Pada Kasus Bronkopneumonia Anak di Rumah Sakit Wijaya Kusuma Lumajang - Ayu Nur A’ida; Rakhmad Rosadi; M. Fashihullisan (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Bronchopneumonia is an infection that affects the airways entering the lungs, also known as the bronchi. Symptoms that arise are cough, fever, restlessness, dyspnea, rapid and shallow breathing, and cyanosis around the nose and mouth. Physiotherapy measures in the form of breathing exercises (deep breathing exercise and coughing) and postural drainage are appropriate interventions for this condition. The aim of the research was to determine the effect of physiotherapy interventions in the form of breathing exercise (deep breathing exercise and coughing) and postural drainage on children's brochopneumonia conditions at Wijaya Kusuma Lumajang Hospital. The research instrument used the Dalhousie Dyspnea Scales. The results of the study showed a decrease in the degree of shortness of breath from 5 to 2 with 8 treatments. So it can be concluded that breathing exercise and postural drainage are effective in reducing the degree of shortness of breath in bronchopneumonia patients